Positive electrode material of supercapacitor and preparation method of positive electrode material
By preparing the positive electrode material of cobalt phosphide supercapacitor and forming a honeycomb structure by low-temperature calcination method, the problem of insufficient energy density and cycle stability of existing electrode materials is solved, and high specific capacitance and good cycle stability are achieved. It is suitable for super High performance applications of capacitors.
Patent Information
- Application Number
- CN202410164218.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-05
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-02-05
AI Technical Summary
Existing supercapacitor electrode materials have shortcomings in terms of energy density and cyclic stability, especially the high cost and short life of transition metal compound materials, as well as the volume expansion and contraction of conductive polymer materials, which affect their electrochemical properties.
By preparing the positive electrode material of the cobalt oxyphosphide supercapacitor, two calcining methods were performed at low temperatures using the ZIF-67 precursor and sodium hypophosphite to form a cobalt oxyphosphide material with a micro-nano-scale honeycomb structure, and on the foam nickel Prepare electrode sheets, combine acetylene carbon black and polytetrafluoroethylene emulsion for covering to improve the electrochemical properties of the material.
It achieves high specific capacitance, good cycling stability and small internal resistance. The material maintains an initial specific capacitance of 93.81% at high current density, and the equivalent series resistance is 0.66Ω, which is suitable for high-performance applications of supercapacitors.
Smart Images

Figure BDA0004699292230000071 
Figure HDA0004699292240000011 
Figure HDA0004699292240000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials for supercapacitors, and the present invention relates to a positive electrode material for supercapacitors and a preparation method thereof, and specifically to a positive electrode cobalt oxyphosphide electrode material for supercapacitors and a preparation method thereof. Background Art
[0002] Supercapacitors are a new type of environmentally friendly energy storage device with advantages such as excellent energy output capacity, long service life, and fast charging and discharging speed. In recent years, research on supercapacitors has been continuously strengthened, and related technology industries have developed rapidly, with broad market prospects. However, supercapacitors have the disadvantage of low energy density. An effective solution is to research and develop electrode materials with high conductivity and good electrochemical activity. Supercapacitors are electrochemical devices that can be used to store energy, and their working principle is different from that of traditional chemical batteries. According to the basic working principle of storing charge, supercapacitors can be divided into double-layer capacitors and pseudocapacitors. Double-layer capacitors are generated by the adsorption of anions and cations at the electrode / electrolyte interface. Double-layer capacitors release and store charges through physical processes, and have high power density, good cycle performance and rate capability, but their energy density is not high. The pseudocapacitor effect was originally proposed by Faraday, and electrical energy is efficiently stored through rapid redox reactions on the electrode surface. The electrode materials of pseudocapacitors can show higher energy density because of their fast Faraday characteristics.
[0003] Electrode materials are the main factors affecting the electrochemical performance of supercapacitors. There are three main types of commonly used supercapacitor electrode materials: carbon-based materials, transition metal compounds (oxides, sulfides, etc.) and conductive polymer materials. These electrode materials have their own advantages and disadvantages: carbon-based materials have good cycle stability, simple process, low cost, but low specific capacity; transition metal compound materials have much higher specific capacity than carbon materials, but higher cost, short life and certain toxicity; conductive polymer materials have good electronic conductivity, small internal resistance and high specific capacity, but are prone to volume expansion and contraction during the cycle process, and have poor cycle stability. Therefore, the development of new electrode materials with multiple advantages is of great significance for the development of supercapacitors. Summary of the invention
[0004] Due to differences in preparation methods, the synthesized electrode materials will differ in appearance, and this factor seriously affects the electrochemical performance of the material. Although transition metal compounds have a high theoretical specific capacitance, they often have fewer active sites due to their appearance and morphology, which seriously affects their electrochemical energy storage effect and cannot achieve the theoretical effect. Resulting in very poor specific application effects. In order to overcome the deficiencies of the prior art, the present invention provides a supercapacitor positive electrode material and a preparation method thereof, specifically a cobalt oxyphosphide supercapacitor electrode material and a preparation method thereof.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] A cobalt oxyphosphide supercapacitor positive electrode material and a preparation method thereof, comprising the following steps:
[0007] Step (1) Preparation of ZIF-67 precursor:
[0008] Dissolve 0.004-0.006 mol of Co(NO3)2·6H2O and 0.0046-0.006 mol of C4H6N2 in anhydrous methanol, add the C4H6N2 solution to the pink Co(NO3)2 solution, and stir under magnetic stirring for 2-4 hours. Centrifuge for 5-10 minutes to obtain the purple product ZIF-67 precursor, then wash it with distilled water and anhydrous ethanol for 3 times each, dry it at 60°C for 12 hours, and set aside.
[0009] Step (2) Preparation of Co3O4-12:
[0010] The ZIF-67 precursor prepared in step (1) is placed in an electrically heated tubular furnace and calcined in an environment in contact with air. After calcination, the precursor is cooled to room temperature to obtain dodecahedral Co3O4-12 derived from ZIF-67.
[0011] Step (3) Preparation of cobalt oxyphosphide material:
[0012] 0.1 g of Co3O4-12 and 0.5-1 g of sodium hypophosphite were placed in two porcelain boats, which were then placed in an electrically heated tube furnace and heated at 5 °C min in a nitrogen atmosphere. -1 When the temperature reaches 350°C, keep it for 2 to 4 hours. Cool it to room temperature to obtain cobalt oxyphosphide material.
[0013] Furthermore, the magnetic stirring rate in step (1) is 100 to 300 r / min; and the centrifuge speed is 4000 to 10000 r / min.
[0014] Furthermore, in the step (2), the calcination temperature in the tubular furnace is 350-400° C., the heating rate is 5° C. / min, and the heat preservation time is 2 hours.
[0015] Furthermore, in the step (3), the nitrogen flow rate in the nitrogen atmosphere is 50-200 mL / min. In the cobalt oxyphosphide electrode material, the approximate atomic ratio of oxygen, phosphorus and cobalt is 3:2:1, and it is a micro-nano honeycomb structure with an equivalent diameter of 0.1-0.2 um.
[0016] The electric heating tube furnace is not limited to any model.
[0017] The present invention also requests protection for the electrochemical application of the positive electrode material prepared by the above preparation method, specifically, the cobalt oxyphosphide material is mixed with acetylene carbon black and polytetrafluoroethylene emulsion in a mass ratio of 8:1:1 and evenly covered on nickel foam (NF), and the nickel foam is pressed by a tablet press to obtain a cobalt oxyphosphide / NF electrode.
[0018] The preferred mass of cobalt oxyphosphide is 0.1-0.15 g, and a cobalt oxyphosphide nickel foam electrode sheet (cobalt oxyphosphide / NF) is obtained, the specification of which is 1 cm×1 cm.
[0019] The present invention is based on Co3O4 nanomaterials, and utilizes P atoms to enter transition metal crystals to change the properties of the metal to improve the electrochemical properties of the material. A new type of cobalt oxyphosphide material is prepared by two low-temperature calcination methods. Nickel foam is used as a substrate, and an electrode sheet is prepared on the nickel foam. The chemical properties of the material are then tested using cyclic voltammetry (CV), constant current charging (GCD) and electrochemical impedance spectroscopy (EIS). The present invention enables supercapacitors to have higher energy density and power density, and is a successful strategy to improve the electrochemical performance of supercapacitors. The improvement of the appearance morphology of electrode materials is one of the important factors for improving electrochemical performance. The present invention aims to explore the control of material morphology by rationally designing electrode materials, and provides a new method for preparing high-capacity energy storage materials using a low-temperature phosphating method.
[0020] The beneficial effects of the present invention compared with the prior art are:
[0021] (1) The material prepared by the present invention has a unique honeycomb structure, which can provide more active sites in the electrochemical charge and discharge process and provide a buffer space to solve the volume expansion of the material during the charge and discharge process.
[0022] (2) The present invention rationally designs electrode materials to control material morphology, utilizes P atoms to enter transition metal crystals, and changes the properties of the metal to improve the electrochemical properties of the material. A new type of cobalt oxyphosphide material is prepared by two low-temperature calcinations at a relatively low temperature (350-400°C). The method is scientific and reasonable, safe and easy to operate, with simple equipment and low cost. The product morphology and structure are controllable, and it is suitable for mass production of cobalt oxyphosphide electrode materials.
[0023] (3) The material CoP2O3 prepared in the present invention is used as a positive electrode material, and exhibits excellent electrochemical performance in the field of supercapacitors, showing high specific capacitance, excellent cycle stability and small internal resistance. -1 At a current density of 1.37 W, the specific capacitance reaches 359.31 F·g -1 ; at 10A·g -1 At the current density, after 2000 cycles, the material still has a 93.81% retention rate of the initial specific capacitance; the equivalent series resistance R s The present invention provides a new idea for the influence of material surface morphology on the performance of supercapacitor electrodes and for the design and development of high-performance supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the preparation of CoP2O3 of the present invention.
[0025] Figure 2 This is a scanning electron microscope (SEM) image of a portion of the material prepared in Example 1 of the present invention. Figure 2 (a) and (b) are SEM images of Co3O4-12 at magnifications of 10,000 times and 21,000 times. Figure 2 (c) and (d) are SEM images of CoP2O3 at magnifications of 10,000 times and 30,000 times.
[0026] Figure 3 The element surface distribution diagram of the CoP2O3 material prepared in Example 1 of the present invention. Figure (a) is the overall mapping diagram of CoP2O3; Figure (b) is the C element distribution diagram; Figure (c) is the Co element distribution diagram; Figure (d) is the P element distribution diagram.
[0027] Figure 4 This is the X-ray powder diffraction pattern of Co3O4-12 and CoP2O3 materials prepared in Example 1 of the present invention.
[0028] Figure 5The electrochemical test results of the application performance of the CoP2O3 material prepared in Example 1 of the present invention are as follows: (a) CV graph at different voltages; (b) CV graph at different scan rates; (c) GCD graph at different current densities; (d) comparison graph of specific capacitance at different current densities; (e) EIS graph; (f) graph of capacitance retention after 2000 charge and discharge cycles. DETAILED DESCRIPTION
[0029] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.
[0030] Example 1
[0031] A cobalt oxyphosphide supercapacitor electrode material and a preparation method thereof, specifically comprising the following steps:
[0032] (1) Preparation of ZIF-67 precursor:
[0033] Dissolve 1.164g Co(NO3)2·6H2O and 1.310g C4H6N2 in 50mL anhydrous methanol. When the solution becomes transparent, add the C4H6N2 solution to the pink Co(NO3)2 solution and stir under magnetic stirring for 2h. Centrifuge for five minutes to obtain the purple product ZIF-67 precursor, then wash it three times with distilled water and anhydrous ethanol, dry it at 60℃ for 12h, and set aside.
[0034] (2) Preparation of Co3O4-12:
[0035] The prepared ZIF-67 precursor was placed in an electrically heated tubular furnace and calcined in an environment exposed to air at 5 °C·min -1 The sample was heated at a rate of 100 °C and kept at 350 °C for 2 hours before cooling to room temperature. Thus, dodecahedral Co3O4-12 derived from ZIF-67 was obtained.
[0036] (3) Preparation of CoP2O3 materials:
[0037] 0.1 g of Co3O4-12 and 0.8 g of sodium hypophosphite were placed in two porcelain boats, which were then placed in an electrically heated tube furnace and heated at 5 °C min in a nitrogen atmosphere. -1 When the temperature reaches 350°C, keep it for 4 hours. Cool it to room temperature to obtain cobalt oxyphosphide material, which is expressed as CoP2O3 according to the atomic ratio of each element. The preparation process of the whole material is as follows Figure 1 shown.
[0038] The morphology of Co3O4-12 and CoP2O3 materials obtained by SEM is shown in Figure 2 shown. Figure 2 (a) and (b) are the morphologies of Co3O4 crystal particles at magnifications of 10,000 times and 21,000 times. It can be seen that the crystals are well distributed and have a dodecahedral structure. Figure 2 Figures (c) and (d) show the morphology of CoP2O3 crystal particles generated by low-temperature calcination of Co3O4-12 crystal particles at 10,000 and 30,000 times magnification. Although the regular octahedron cannot be seen, it can be roughly seen that the shape is a column with two upper and lower bottom surfaces and six sides. The octahedral particle shape of CoP2O3 partially collapses and deforms after phosphating treatment, and the surface area increases. It can be seen that it has good uniformity, and the shape of multiple crystals aggregate is similar to a honeycomb.
[0039] Figure 3 This is the element surface distribution map of CoP2O3 material. Figure 3 (a) is the overall mapping diagram of the CoP2O3 material sample, showing the structure of the CoP2O3 material and the uniform distribution between different nanoparticles. Figure 3 (b) Indicates that the base of the material is C element. Figure 3 (c) and (d) show that the distribution of Co and P elements in CoP2O3 material is basically uniform.
[0040] By first synthesizing Co3O4-12 nanomaterials and then phosphating to synthesize CoP2O3 materials, the XRD patterns of these two materials are shown in Figure 2. Figure 4 As shown, the diffraction peaks at 2θ=19°, 31.27°, 36.85°, 44.81°, 55.66°, 59.36°, and 65.24° correspond to the diffraction peaks of the product before phosphating, which can be attributed to the (111), (220), (311), (400), (422), (511), and (440) crystal planes of Co3O4-12. After the product is phosphated, a diffraction peak appears at 47.12°, which corresponds to the (400) crystal plane of CoP2O3. It can be seen from the figure that the Co3O4-12 nanomaterial is well crystallized.
[0041] Comparative Example 1
[0042] A cobalt oxyphosphide supercapacitor electrode material and a preparation method thereof, specifically comprising the following steps:
[0043] (1) Preparation of ZIF-67 precursor:
[0044] Dissolve 1.171g Co(NO3)2·6H2O and 1.313g C4H6N2 in 50mL anhydrous methanol. When the solution becomes transparent, add the C4H6N2 solution to the pink Co(NO3)2 solution and stir under magnetic stirring for 3h. Centrifuge for five minutes to obtain the purple product ZIF-67 precursor, then wash it three times with distilled water and anhydrous ethanol, dry it at 80℃ for 12h, and set aside.
[0045] (2) Preparation of Co3O4-12:
[0046] The prepared ZIF-67 precursor was placed in an electrically heated tubular furnace and calcined in an environment exposed to air at 5 °C·min -1 The sample was heated at a rate of 100 °C and kept at 360 °C for 2 hours before cooling to room temperature. Thus, dodecahedral Co3O4-12 derived from ZIF-67 was obtained.
[0047] (3) Preparation of cobalt oxyphosphide materials:
[0048] 0.1 g of Co3O4-12 and 0.5 g of sodium hypophosphite were placed in two porcelain boats, which were then placed in an electrically heated tube furnace and heated at 5 °C min in a nitrogen atmosphere. -1 The temperature was heated at a rate of 1.000 ℃. When the temperature reached 360℃, it was maintained for 2 hours. After cooling to room temperature, a cobalt oxyphosphide material was obtained, which was expressed as CoPO3 according to the atomic ratio.
[0049] Comparative Example 2
[0050] A cobalt oxide supercapacitor electrode material and a preparation method thereof, specifically comprising the following steps:
[0051] (1) Preparation of ZIF-67 precursor:
[0052] Dissolve 1.164g Co(NO3)2·6H2O and 1.310g C4H6N2 in 50mL anhydrous methanol. When the solution becomes transparent, add the C4H6N2 solution to the pink Co(NO3)2 solution and stir under magnetic stirring for 3h. Centrifuge for five minutes to obtain the purple product ZIF-67 precursor, then wash it three times with distilled water and anhydrous ethanol, dry it at 80℃ for 12h, and set aside.
[0053] (2) Preparation of Co3O4-12:
[0054] The prepared ZIF-67 precursor was placed in an electrically heated tubular furnace and calcined in an environment exposed to air at 5 °C·min -1The sample was heated at a rate of 100 °C and kept at 350 °C for 2 hours before cooling to room temperature. Thus, dodecahedral Co3O4-12 derived from ZIF-67 was obtained.
[0055] Application Example 1
[0056] The CoP2O3 material prepared in Example 1 was mixed with acetylene carbon black and polytetrafluoroethylene emulsion in a mass ratio of 8:1:1 and evenly coated on the nickel foam, and the nickel foam was pressed for 2 minutes at 7 MPa using a tablet press to obtain a cobalt oxy(phosphide) nickel foam electrode sheet.
[0057] The prepared cobalt oxide (phosphide) nickel foam electrode was used as the working electrode, the metal platinum sheet and the mercury-mercury oxide electrode were used as the counter electrode and the reference electrode respectively. A three-electrode system was assembled using 6 mol / L KOH as the electrolyte, and cyclic voltammetry and constant current charge-discharge experiments were carried out. The specific capacitance C at different current densities was calculated according to formula (1), and a cycle stability experiment was carried out to detect the electrochemical properties of the material.
[0058] C=IΔt / mΔV Formula (1)
[0059] Where I is the discharge current (A), Δt is the discharge time (s), ΔV is the voltage range (V) and m is the mass of active material (g).
[0060] The specifications of the metal platinum sheet electrode are 2cm×2cm; the cyclic voltammetry potential range is 0.0~0.5V; the constant current charge and discharge potential range is 0.1~0.5V.
[0061] Application Comparative Example 1
[0062] The CoPO3 material prepared in Comparative Example 1 was mixed with acetylene carbon black and polytetrafluoroethylene emulsion in a mass ratio of 8:1:1 and evenly coated on the nickel foam, and the nickel foam was pressed for 2 minutes at 7 MPa using a tablet press to obtain a cobalt oxy(phosphide) nickel foam electrode sheet.
[0063] The rest is the same as Application Example 1.
[0064] Application Comparative Example 2
[0065] The Co3O4-12 material prepared in Comparative Example 2 was mixed with acetylene carbon black and polytetrafluoroethylene emulsion in a mass ratio of 8:1:1 and evenly coated on the nickel foam, and the nickel foam was pressed for 2 minutes at 7 MPa using a tablet press to obtain a cobalt oxy(phosphide) nickel foam electrode sheet.
[0066] The rest is the same as Application Example 1.
[0067] The corresponding three materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used as working electrodes in Application Example 1, Application Comparative Example 1 and Application Comparative Example 2 for electrochemical testing, and the results are shown in Table 1.
[0068] Table 1. Electrochemical test results
[0069]
[0070] It can be seen from Table 1 that the CoP2O3 prepared in Example 1 has the best electrochemical performance, the highest specific capacitance and the smallest equivalent series resistance, indicating that the electrochemical energy storage performance of the material that is fully phosphated is greatly improved.
[0071] The CoP2O3 material prepared in Example 1 was subjected to more detailed electrochemical tests, and an asymmetric supercapacitor was assembled with CoP2O3 / NF as the positive electrode and commercial activated carbon (AC) as the negative electrode, and a two-electrode electrochemical test was performed with 6 mol / L KOH as the electrolyte.
[0072] The energy density and power density are calculated as follows:
[0073] E=C(△V) 2 / 7.2 Formula (2)
[0074] P=3600E / △t Formula (3)
[0075] Where E is the energy density (W h / kg), △t is the discharge time (s), P represents the power density (W / kg), △V is the charge and discharge voltage range (V), and C is the specific capacitance value C.
[0076] The CV graphs of CoP2O3 materials at different voltages are shown in the figure Figure 5 The results show that the area of the CV curve is the largest in the voltage range of 0.0 to 0.55 V, but the tail of the curve peak is too sharp, so the test voltage range is selected as 0.0 to 0.5 V. Figure 5 (b) The CV curve shows that CoP2O3 / NF exhibits the characteristics of pseudocapacitance and dual capacitance, mainly showing dual capacitance characteristics, while the pseudocapacitance characteristics are not obvious, so the redox peak in this figure is not obvious. Figure 5 (c) GCD curves of CoP2O3 / NF materials at different scan rates. -1 , 1A·g -1 , 2A·g -1 , 5A g -1 and 10A·g -1 At a current density of , the specific capacitance is 359.31F·g -1 、320.24F·g -1、277.32F·g -1 、240.57F·g -1 and 209.78 F·g -1 . Figure 5 (d) shows the specific capacitance comparison of CoP2O3 / NF at different current densities. It can be seen that the current density increases from 0.5 to 10 A·g -1 When the specific capacitance value is maintained at 58.4%, the retention rate of the specific capacitance reaches 58.4%. This shows that the electrode has good rate characteristics. Compared with Co3O4-12, the specific capacitance values of CoP2O3 / NF are greatly improved at different current densities, and it shows good rate characteristics, indicating that the electrochemical energy storage performance of the material is greatly improved after phosphating. Electrochemical impedance spectroscopy (EIS) was used to characterize the CoP2O3 / NF material, revealing the rate of ion transmission on the electrode surface and the transport kinetics of charge diffusion in the material, with a frequency range of 0.01 to 10 5 Hz. Figure 5 The semicircle diameter and the slope of the line in (e) reflect the conductivity of the material and the contact between CoP2O3 and the NF current collector, respectively. The AC impedance data was simulated using ZSimpWin 3.60 software, and an equivalent circuit model was obtained (inside figure). As can be seen from the figure, the curve formed by the simulated data and the measured original data is very consistent. The equivalent circuit model is composed of R s , W, R ct , C and Q, among which R s Represents the sum of contact resistance and internal resistance of electrode material, W is Warburg impedance, R ct represents the resistance to the movement of ions in the electrode pores and electrolyte. C and Q represent the capacitance and constant phase angle elements in the charge and discharge process, respectively. The equivalent series resistance R in the high frequency region s The equivalent series resistance R is 0.66Ω. s It represents the resistance encountered when the charge is transferred between the active material and the electrolyte. Figure 5 (f) is the cycle life diagram of CoP2O3 / NF, which shows that at 10A·g -1 At the same current density, after 2000 cycles, the material still has 93.81% of the initial specific capacitance.
[0077] The double-electrode electrochemical test assembled into an asymmetric supercapacitor CoP2O3 / NF / / AC / NF with a potential range of 0 to 1.5 V and a power density of 369.09 W·kg -1 The energy density of CoP2O3 / NF / / AC / NF can reach 24.66Wh·kg -1 .
[0078] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a cobalt oxyphosphide supercapacitor positive electrode material, characterized in that: The following steps are involved: Step (1) Preparation of ZIF-67 precursor: Dissolve Co(NO3)2·6H2O and C4H6N2 in anhydrous methanol respectively, add C4H6N2 solution into pink Co(NO3)2 solution, and react with magnetic stirring for 2-4 hours; centrifuge for 5-10 minutes to obtain purple product ZIF-67 precursor, and then wash with distilled water and anhydrous ethanol, dry and set aside; Step (2) Preparation of Co3O4-12: The ZIF-67 precursor prepared in step (1) is placed in an electrically heated tubular furnace and calcined in an environment in contact with air; after calcination, it is cooled to room temperature to obtain dodecahedral Co3O4-12 derived from ZIF-67; Step (3) Preparation of cobalt oxyphosphide material: Co3O4-12 and sodium hypophosphite were placed in two porcelain boats, which were then placed in an electrically heated tube furnace and heated at 5 °C min in a nitrogen atmosphere. -1 The method comprises heating the mixture at a rate of 350° C. and maintaining the temperature for 2 to 4 hours. The mixture is cooled to room temperature to obtain a cobalt oxyphosphide material.
2. A method for preparing a cobalt oxyphosphide supercapacitor positive electrode material as claimed in claim 1, characterized in that: The magnetic stirring rate in step (1) is 100 to 300 r / min.
3. The method for preparing a cobalt oxyphosphide supercapacitor positive electrode material according to claim 1, characterized in that: The centrifuge speed is 4000~10000r / min.
4. The method for preparing a cobalt oxyphosphide supercapacitor positive electrode material according to claim 1, characterized in that: In the step (2), the calcination temperature in the tubular furnace is 350-400°C, the heating rate is 5°C / min, and the temperature is kept for 2 hours.
5. The method for preparing a cobalt oxyphosphide supercapacitor positive electrode material according to claim 1, characterized in that: In the step (3), the nitrogen flow rate in the nitrogen atmosphere is 50-200 mL / min.
6. A method for preparing a cobalt oxyphosphide supercapacitor positive electrode material as claimed in claim 1, characterized in that: In the step (1), the product is washed with distilled water and anhydrous ethanol three times each, and dried at 60° C. for 12 hours.
7. Electrochemical application of a positive electrode material prepared by the method for preparing a cobalt oxyphosphide supercapacitor positive electrode material according to any one of claims 1 to 6.
8. The use according to claim 8, characterized in that: Specifically, the cobalt oxyphosphide material, acetylene carbon black and polytetrafluoroethylene emulsion are mixed in a mass ratio of 8:1:1 and evenly covered on the nickel foam. The nickel foam is pressed by a tablet press to obtain the cobalt oxyphosphide / NF electrode.
Citation Information
Patent Citations
Preparation method of polyhedral cobalt phosphide catalyst for hydrogen production through water electrolysis
CN105107536A
Preparation method of cobalt phosphide hollow nano-fiber material
CN105803580A
Preparation method for preparing Co3O4@CoP composite electrode based on MOF template
CN105977467A
MOF-derived cobaltosic oxide, cobalt oxide and dicobalt phosphide composite material as well as preparation method and application thereof
CN116920954A
Cobalt phosphorus-cobalt oxide composite electrode material and application thereof
CN116960367A
